Seeking a preferential option for the rural poor in Chile - Edward Dew (Ciências Sociais Unisinos)
From colonial times well into the twentieth century (and, unfortunately, even beyond) the man/land relationship in Latin America has been markedly unjust. Small numbers of families have owned large tracts of the best land, while large numbers of poor families have struggled with tiny plots of marginal land or labored on the estates of the rich. Chile was no exception to this pattern. Thus, its experiment with land reform in the 1960s and 1970s, the setback of reform under the military in the 1970s and 1980s, and the resumption of reform under democrats in the 1990s, may provide lessons for the rest of Latin America. Is a preferential option for the rural poor still possible in a neoliberal economic system? In Chile, the answer is a qualified yes